2004
DOI: 10.1016/j.eurpsy.2004.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-associated mania with escitalopram

Abstract: appeared when the diuretic was withheld. The treatment strategy was then changed to taper the dosage of amusulpride from 800 to 400 mg per day and to stop using the diuretic. Within one week with this strategy, the bilateral pedal edema resolved entirely. The patient's psychiatric condition remained stable on this dosage of amisulpride. In our case, treatment of amisulpride alone or an adverse interaction between amisulpride and lorazepam may be responsible for the patient's bilateral pedal edema. The latter i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…10 Cases of mania have been reported under escitalopram therapy in patients with no history of mania. 11,12 In the present case, because the patient had taken escitalopram for 6 months, the risk for a switch to mania was decreased but remained still possible, particularly in the absence of a mood stabilizer. Of note, the patient was previously treated with the antidepressant fluoxetine for at least 2 years without a manic switch.…”
Section: Discussionmentioning
confidence: 59%
“…10 Cases of mania have been reported under escitalopram therapy in patients with no history of mania. 11,12 In the present case, because the patient had taken escitalopram for 6 months, the risk for a switch to mania was decreased but remained still possible, particularly in the absence of a mood stabilizer. Of note, the patient was previously treated with the antidepressant fluoxetine for at least 2 years without a manic switch.…”
Section: Discussionmentioning
confidence: 59%
“…Although it is also considered to have fewer adverse effects than other SSRIs, 42 , 43 escitalopram-induced mania/hypomania has been documented in a few case reports and in one clinical trial. 32 – 34 Historically, the rate of SSRI treatment-emergent mania has been estimated at 3%–6% in bipolar depression and less than 3% in major depressive disorder. 5 , 6 , 44 Previous studies have identified several risk factors for antidepressant-induced manic switch, such as signs of bipolarity and family history of bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Among SSRIs, escitalopram possesses the greatest serotonin transporter (5-HTT) selectivity, 29 with fewer adverse effects than other SSRIs. 30 , 31 While treatment-emergent mania/hypomania has been reported in a few clinical cases and one clinical trial, 32 – 34 it remains unknown whether this effect is dose-related.…”
Section: Introductionmentioning
confidence: 99%